Can Green Finance Effectively Promote the Carbon Emission Reduction in “Local-Neighborhood” Areas?—Empirical Evidence from China - Sun, Jing; Zhai, Ningning; Miao, Jichao; Sun, Huaping (Agriculture (Basel), 2022)
Carbon emission reduction is a systematic project requiring support from policy, capital, and technology in its promotion, which represents a greater need for green finance. Frontier research focuses on the impact of green finance on local CO2 emissions, but generally ignores its ripple impacts on carbon emission reduction in adjacent areas. Combining panel data from 30 Chinese provincial-level cities from 2004 to 2019, this study employs a spatial panel Durbin model to empirically test the ripple effect of green finance on carbon emission reduction in adjacent areas and further investigate the formation mechanism of the ripple effect. The results are as follows: (1) Green financial development has a significant inhibitory effect on local and neighboring CO2 emissions, which affirms the existence of the ripple effect of green finance. (2) Through formation mechanism analysis, it is found that the upgrading of an industrial structure has played a transmission role in the ripple effect of green finance. Finally, based on the empirical results, some suggestions are put forward from the perspectives of innovating green financial services and promoting the effective alignment of green financial development with carbon emission reduction targets and the deep integration of green finance and regional green industry development, so as to better develop the potential of green finance in the realization of the carbon reduction goals.